FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN PERAWAT DALAM PEMAKAIAN ALAT PELINDUNG DIRI (APD) SELAMA MASA PANDEMI COVID-19 DI RSUD dr. H. IBNU SUTOWO BATURAJA TAHUN 2021 - Rum, Listia Ning (JURNAL KESEHATAN INDRA HUSADA, 2021)
Introduction: Personal protective equipment is a tool that serves to protect workers against exposure to hazards that cause illness and death in workers in the work environment. The purpose of this study was to determine the factors related to Nurse Compliance in the Use of Personal Protective Equipment (PPE) During the COVID-19 Pandemic Period at Hospital. Dr. H. Ibnu Sutowo Baturaja in 2021. Method: This research uses Quantitative research design with cross sectional analytic survey method. The population in this study were employees at RSUD Dr. H. Ibnu Sutowo Baturaja in 2021. The sampling of this research was determined by purposive sampling, namely the employees of the RSUD Dr. H. Ibnu Sutowo Baturaja each as many as 76 respondents. Data collection by using a questionnaire. Results: There is a significant relationship for the variables Knowledge (p value 0.03) and motivation (p value 0.03). From the results of the multivariate statistical test, the dominant factor was obtained, the knowledge variable (p value 0.03) with an OR value (5.79). Conclusion: Knowledge is the dominant factor in nurse compliance in the use of PPE. Keywords: Personal Protective Equipment, Compliance and Hospital